Behavioural linear standardized scoring system of the Lidia cattle breed by testing in herd: estimation of genetic parameters. (17th December 2015) - Pelayo, R.; Solé, M.; Sánchez, M.J.; Molina, A.; Valera, M.
Summary: Docility is very important for cattle production, and many behavioural tests to measure this trait have been developed. However, very few objective behavioural tests to measure the opposite approach' aggressive behaviour' have been described. Therefore, the aim of this work was to validate in the Lidia cattle breed a behavioural linear standardized scoring system that measure the aggressiveness and enable genetic analysis of behavioural traits expressing fearless and fighting ability. Reproducibility and repeatability measures were calculated for the 12 linear traits of this scoring system to assess its accuracy, and ranged from 85.3 and 94.2%, and from 66.7 to 97.9%, respectively. Genetic parameters were estimated using an animal model with a Bayesian approach. A total of 1202 behavioural records were used. The pedigree matrix contained 5001 individuals. Heritability values (with standard deviations) ranged between 0.13 (0.04) (Falls of the bull) and 0.41 (0.08) (Speed of approach to horse). Genetic correlations varied from 0.01 (0.07) to 0.90 (0.13). Finally, an exploratory factor analysis using the genetic correlation matrix was calculated. Three main factors were retained to describe the traditional genetic indexes aggressiveness, strength and mobility.